Very early symptomatic metastasis pseudoprogression after stereotactic brain radiosurgery in a melanoma patient treated with BRAF/MEK inhibitors: a case report and review of the literature - Romano, Edouard; Tran, Sebastien; Ben Aissa, Assma; Carvalho Goncalves, Miguel; Durham, André; Tsoutsou, Pelagia (Frontiers in Oncology, 2024)
IntroductionSignificant therapeutic changes have recently occurred in the management of melanoma brain metastases (BMs), both in the field of local treatments, with the rise of stereotactic radiotherapy (RT), as well as in systemic ones, with the advent of immunotherapy and targeted therapies (TT). These advances have brought about new challenges, particularly regarding the potential interactions between new TT (notably BRAF/MEK inhibitors) and irradiation. Through a clinical case, we will discuss a side effect not previously described in the literature: ultra-early pseudoprogression (PP) following brain stereotactic radiosurgery (SRS), in a patient treated with dabrafenib-trametinib.Case presentationA 61-year-old patient with BRAFV600E-mutated melanoma, receiving second-line dabrafenib-trametinib therapy, was referred for SRS on three progressing meningeal implants, without evidence of systemic progression. Four days after the first RT session (1x6 Gy on a fronto-orbital lesion prescribed 5x6 Gy, and 1x20 Gy single fraction on the other lesions), the patient presented with an epileptic seizure. An MRI, compared to the planning MRI ten days earlier, revealed significant progression of the irradiated lesions. The patient’s condition improved with dexamethasone and levetiracetam, and RT was halted out of caution. A follow-up MRI at one month demonstrated a size reduction of all treated lesions. Subsequent imaging at five months revealed further shrinking of the two lesions treated with an ablative dose of 20 Gy, while the under-treated fronto-orbital lesion progressed. These dynamics suggest an initial PP in the three irradiated lesions, followed by good response in the ablatively treated lesions and progression in the partially treated lesion.ConclusionTo our knowledge, this represents the first documented case of ultra-early PP following brain SRS in a patient receiving concomitant dabrafenib-trametinib. It highlights the need for particular vigilance when using tyrosine kinase inhibitors (TKIs) with SRS, and warrants further research into potential treatment interactions between RT and novel systemic agents, as well as the optimal treatment sequence of melanoma BMs.